The Contribution of Art Education to Creativity: From Individual Development to Social Integration - Özaltun, Gözde (Universitas Komputer Indonesia, 2025)
Art education assumes a fundamental function in developing individuals' creative thinking capacities and transferring these skills to interdisciplinary life practices. Research shows that the creativity gained in the process of art education is not limited to aesthetic production; it is also directly related to high-level thinking skills such as critical analysis, innovative problem solving, cognitive flexibility and interdisciplinary synthesis. This process nourishes not only the cognitive competencies of the individual, but also the social skills that form the basis of collective life such as empathy, cooperation and social dialogue. Therefore, art education functions as a sociocultural bridge that enables individuals to interact harmoniously and effectively with social systems. Individuals who use the liberating potential of creative expression acquired through art education also gain the ability to develop sensitivity to social problems and to produce collective solutions. In addition, it can be said that art education, beyond being a mere aesthetic experience, is a powerful tool in gaining sensitivity to social problems and creating collective awareness. The study emphasises the indispensable role of art education within the general education paradigm. Based on its effects on individuals' cognitive skills, it has been demonstrated that art education contributes not only to individual development but also to social integration and cultural sustainability in multiple ways. Art education has been evaluated as a lifelong learning process and has emerged as a continuous area of development that can be related to the individual's experiences. In this context, it has been concluded that art education should be positioned as a strategic learning area that supports individual potential, encourages social development, and increases cultural, aesthetic, and social awareness from pre-school onwards. Keywords: Art Education, Creativity, Creative Thinking, Cognitive Development, Interdisciplinary Education